A Blockchain Based Decentralized Identifiers for Entity Authentication in Electronic Health Records. Issue 1 (31st December 2022) - T, Manoj; Makkithaya, Krishnamoorthi; V G, Narendra
Abstract: Over the past two decades, the fast pace of digitization in the healthcare ecosystem led to a phenomenal rise in the creation, storage and sharing of Electronic Health Records (EHRs) across the globe. However, the mechanism of authentication used for proving the identity of entities in EHRs is based on the identifiers issued by centralized identity providers (IDPs). It may lead to a single point of failure, loss of privacy and lack of interoperability. A new wave of decentralized identifiers (DIDs) and verifiable credentials(VCs) data modelled by blockchain has made it possible to achieve entity authentication in a decentralized manner. In this study, a blockchain-based framework with decentralized identifiers for patient authentication and consent management for EHR access using verifiable credentials is proposed. It describes the process of DID generation and authentication credential setup along with workflows for issuing and verifying credentials in the EHR ecosystem. The framework is implemented using Hyperledger Indy blockchain and Aries library. The study evaluates the performance of proposed workflows in terms of scalability, efficiency, resource utilization and conducts security analysis. Specifically, the outcome of this study can be used to realize the decentralized identity management and authentication in EHR systems.